Co-authorship in Management Journals: Ethical Rules for Scientific Research - Risso, Mario (Symphonya, 2024)
In recent years, there has been a gradual increase in the number of research collaborations and the production of scientific articles. To date, few studies have analysed this phenomenon in the field of management sciences. This paper presents an exploratory analysis of the phenomenon, with a focus on the production of articles in 12 leading journals in the field of management. Data reveals a twofold phenomenon: firstly, the exponential multiplication of articles in some top journals, and secondly, the near disappearance of articles with a single author and the concomitant growth of articles attributed to five or more authors. This trend gives rise to the necessity of addressing ethical and practical aspects in order to cope with the phenomenon, which could otherwise undermine the reputation and quality of scientific production in management.